AKTUALISASI PROGRAM KAMPUS MENGAJAR SEBAGAI WADAH KONTRIBUSI MAHASISWA TERHADAP PENDIDIKAN DASAR DI SD NEGERI KEDUNGMEGARIH - Arneta Mei Vella; Novi Darmayanti; Yustin Nur Faizah (LPPM Universitas Islam Darul 'Ulum Lamongan, 2023)
Students as agents of change in improving human resources by contributing and innovating together to help society. The Merdeka Learning Merdeka Campus (MBKM) program is a program born from the concept of learning freedom that provides a platform for students to grow and contribute, especially in the areas of literacy and numeracy. The Covid-19 pandemic has caused learning loss that has had a major impact on basic education in Indonesia, including students at Kedungmegarih Primary School.The purpose of writing this scientific article is to study the actualization of the campus program as a space for students. contributions to basic education at Kedungmegarih Public Elementary School. This research uses a qualitative approach with descriptive methods. In data collection techniques, authors use documentation techniques in the form of related literature, like books and articles. The results of this study indicate that the Teaching Campus program provides a forum for student contributions as a concrete manifestation of the importance of agents of change so that Teaching Campus activities can have a positive impact on all. the elements involved, especially those around the Kedungmegarih school.